PERAN BADAN KESWADAYAAN MASYARAKAT DAN KELOMPOK SWADAYA MASYARAKAT DALAM PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERDESAAN - Yohanis E Teturan (Universitas Musamus, Merauke, Papua, 2013)
Self-reliance society and the role of The Group of Ngos in the National Programme of independent Rural community empowerment (case study on the village and the village of Ngilngof Subdistrict Namar Kei Kecil Southeast Maluku Regency). This research aims to analyze and describe the effectiveness of self-help group of society and the self-reliance society. There is sufficient community participation and impact of Self-Reliance community in PNMP-MP. The research was carried out in the village and the village of Ngilngof Subdistrict Namar Kei Kecil Southeast Maluku Regency. The methods used in this study is a case study, with the kind of qualitative and descriptive research analysis tool komponensial. Research results show that the role of the community in every group of self-reliance phase of the National community empowerment Programs for rural Independent (PNPM-MP) in Ohoi Namar and Ngilngof Small Town Kei Ohoi Southeast Maluku district has yet to appear because it is still less coordination in activities that are done well it planning stages of implementation to evaluation. Haven't seen the role of the community as a self-reliance and participation of society in any self-reliance activity in do by PNPM-MP and has not seen its impact on the development changes and Ohoi Namar Ngilngof sub-district of Kai Kecil Southeast Maluku Regency